The role of radiation therapy for carcinoma of the lung. - Cox, J. D. (Yale Journal of Biology and Medicine, 1981)
A large proportion of patients with carcinoma of the lung may benefit from the use of radiation therapy. Operable patients have not been shown to benefit from preoperative irradiation, but postoperative irradiation has improved survival in those found to have involvement of hilar or mediastinal lymph nodes. Radiation therapy is the only potentially curative treatment for patients who are inoperable, but do not have distant metastasis. Control of the local tumor is very dependent upon dose-fractionation-time relationships. Patients who are relatively asymptomatic, i.e., they have a high performance status, are curable if treated promptly with radiation therapy. Small cell carcinoma requires both radiation therapy and chemotherapy. The optimal method of combining the two modalities is yet to be determined, but prophylactic cranial irradiation is necessary to control microscopic metastases that are not affected by systemic chemotherapy, and thoracic irradiation is necessary to give the highest probability of control of the primary tumor. Prophylactic cranial irradiation has also been shown to reduce the frequency of brain metastasis in patients with squamous carcinoma, large cell carcinoma, and adenocarcinoma; it may become more important in these cell types when more effective chemotherapy is developed.